Exogenous ethanol induces a metabolic switch that prolongs the survival of Caenorhabditis elegans dauer larva and enhances its resistance to desiccation - Kaptan, Damla; Penkov, Sider; Zhang, Xingyu; Gade, Vamshidhar R.; Raghuraman, Bharath Kumar; Galli, Roberta; Sampaio, Julio L.; Haase, Robert; Koch, Edmund; Shevchenko, Andrej; Zaburdaev, Vasily; Kurzchalia, Teymuras (Aging Cell, 2020)
The dauer larva of Caenorhabditis elegans, destined to survive long periods of food scarcity and harsh environment, does not feed and has a very limited exchange of matter with the exterior. It was assumed that the survival time is determined by internal energy stores. Here, we show that ethanol can provide a potentially unlimited energy source for dauers by inducing a controlled metabolic shift that allows it to be metabolized into carbohydrates, amino acids, and lipids. Dauer larvae provided with ethanol survive much longer and have greater desiccation tolerance. On the cellular level, ethanol prevents the deterioration of mitochondria caused by energy depletion. By modeling the metabolism of dauers of wild-type and mutant strains with and without ethanol, we suggest that the mitochondrial health and survival of an organism provided with an unlimited source of carbon depends on the balance between energy production and toxic product(s) of lipid metabolism.
CRIS-Team Scopus Importer:2020-09-18
Keywords: aging; exogenous ethanol; metabolic shift; mitochondrial health; stress resistance